Impact of a mobile unit on access to eye care in Sao Paulo, Brazil - Satto, Larissa Horikawa [UNESP]; Fernandes de Souza Meneghim, Roberta Lilian [UNESP]; Hirai, Flavio Eduardo; Padovani, Carlos Roberto [UNESP]; Schellini, Silvana Artioli [UNESP] (Consel Brasil Oftalmologia, 2021)
Purpose: The goal of this study was to determine the impact of a mobile eye health unit on access to eye care and to generate a profile of the population requiring ophthalmic care by age, nature of their ophthalmic diseases, and optimal management. Methods: The study was conducted in 14 cities in the southwest region of Sao Paulo, Brazil. Subjects included individuals who participate in the Brazilian Unified Health System who were in need of eye care. There were no restrictions on age, gender or socioeconomic status. Data was transferred to an Excel table for statistical analyses. Results: We evaluated 6,878 participants in this survey with mean age of 44 years (range 4 months to 96 years); 65.5% were female. Among the diagnoses, 78.6% presented with refractive errors, 9.6% presented with cataracts and 8.3% presented with pterygium. New corrective lenses were prescribed for 60.9% of the participants; 10% retained their existing lenses, similar to 28% required counseling only and18.1% of the participants were referred to a tertiary facility for specialized exams and/or surgical procedures. Of the participants who required outside referrals, 36.4% required oculoplastic/external eye surgery and 31.8% required cataract surgery. Conclusion: The vast majority of patients presenting to a mobile eye health unit required prescriptions for corrective lenses. The rate of detection of ocular disorders was relatively high and the mobile unit provided effective treatment of refractive errors and referrals for specialized ophthalmic examinations and procedures. A mobile eye health unit can be an effective alternative method for improving access to basic eye care, for promoting eye health education and preventing blindness.
Keywords: Mobile health units; Eye health; Vision disorders; Refractive errors; Eyeglasses; Blindness/prevention & control